Clinical indications for SPECT/CT - Israel, Ora (Henry Stewart Talks, 2010)
History of SPECT/CT, Pitfalls and sources of errors in SPECT/CT imaging, Referral criteria to SPECT/CT, Clinical SPECT/CT devices, Clinical indications for SPECT/CT: endocrine disease, Neuroendocrine tumors, thyroid cancer, parathyroid adenoma, lymphoscintigraphy, bone imaging in cancer patients, infection and nuclear cardiology, Clinical protocols for SPECT/CT, SPECT/CT: future goals